TALK SHOW UMKM DI RRI: SOLUSI DAN INOVASI UNTUK MENDUKUNG KEBANGKITAN EKONOMI NASIONAL - Wuryandari, Nur Endah Retno; Adiwibowo, Bugi Satrio; Purwanto, Setiyo (Jurnal Abdimas Sangkabira, 2024)
Implementing Community Service (PkM) aims to encourage collaboration and exchange of ideas among Micro, Small, and Medium Enterprises (MSMEs) to present solutions and innovations supporting the national economic recovery through a talk show on RRI PRO 1 FM. The method used in this activity includes organizing a talk show involving MSME actors as resource persons, focusing on discussions about solutions and innovations that can support the growth of MSMEs and their contribution to the national economic recovery. The results of the PkM implementation and its implications show that we have successfully contributed by partnering with MSME actors as companions in sharing experiences, solutions, and innovations that can make a positive contribution to the national economy.